PP32 Major trauma triage tools study (MATTS) expert consensus meetings. Issue 10 (25th September 2020) - Holt, Christopher; Fuller, Gordon; Keating, Samuel; Turner, Janette; Goodacre, Steve; Smith, Jason
Abstract : Introduction: Major trauma triage tools are used to identify patients for bypass to Major Trauma Centres (MTCs). Bypass has been associated with improved patient outcomes following major trauma. The aim of the Major Trauma Triage Tools Study (MATTS) is to produce an evidence-based triage tool to be implemented across UK ambulance services. Methods: Two independently chaired 1-day expert consensus meetings comprised of senior clinical professionals from specialties relevant to major trauma and prehospital triage were conducted as part of Phase 1 of the MATTS project, each with a distinct focus: To define a reference standard of major trauma Produce a new triage tool Facilitated round table discussions were conducted with consensus developed through arbitration. In the first meeting a multi-domain reference standard defining major trauma patients with the potential to benefit from MTC care was determined. In the subsequent meeting triage tools were developed to select appropriate injured patients meeting this reference standard. Results: Three tools were produced with a different diagnostic accuracy focus: Sensitive – Maximising major trauma identification. Specific – Preserving MTC care for the most severely injured patients Balanced – A tool balancing sensitivity and specificity Conclusion: The reference standard will form the basis of data analysis in Phase 2 of the project. The performance of the 3 differing tools will be tested in a dataset of routine ambulance service and TARN data. Following this, the most optimal triage tool will be assessed in clinical practice across 4 ambulance services.